THE EFFECTIVENESS OF USING YOUTUBE VIDEOS OF PROCEDURE TEXT TO IMPROVE STUDENTS’ SPEAKING SKILL - Pratiwi, Duta Aisyah; Atmowardoyo, Haryanto; Talib, Ahmad (JTechLP: Journal of Technology in Language Pedagogy, 2023)
This study aimed to determine the effectiveness of using YouTube videos of procedure text to improve students' speaking skills in the tenth grade of SMAN 5 Enrekang. This research is pre-experimental research involving one class that is given a treatment. The population of this research is the tenth-grade students of SMAN 5 Enrekang. The sample was obtained from the population using the cluster random sampling method where one class, class X KM 8, which consists of 33 students, was selected randomly. The data collection process involved the administration of a speaking pre-test and post-test. The data collected from the speaking oral test was analyzed quantitatively using the IMB SPSS application and was used to compare the pre-test and post-test using the Paired Sample T-test. The analysis results show that the mean pre-test score is 34.36 with a "very poor" classification, and the mean score of the post-test is 60.45 in the "fair" classification. Based on the hypothesis of this study, there is a significant effect of using YouTube videos of procedure text in improving the students' speaking skills in the tenth grade of SMAN 5 Enrekang. Therefore, it can be concluded that the use of YouTube videos of procedure text improves the speaking skills of the students in the tenth grade of SMAN 5 Enrekang.